2020
DOI: 10.1002/nau.24418
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy prevents subarachnoid hemorrhage‐induced apoptosis and impaired contractility of the rabbit bladder

Abstract: Aim To explore the effects of experimental subarachnoid hemorrhage (SAH) on rabbit urinary bladder and to assess the potential protective effects of hyperbaric oxygen therapy (HBOT). Methods A total of 15 male New Zealand white rabbits were divided randomly to one of three groups: group I was spared as the control group (n = 5), group II was exposed to SAH, received no treatment, and acted as the SAH group (n = 5) and group III was exposed to SAH and received five sessions of HBOT (started 12 hours after SAH i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Research has shown potential protective effects of HBOT in both preclinical studies and in various SAH cases as well. [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown potential protective effects of HBOT in both preclinical studies and in various SAH cases as well. [20][21][22].…”
Section: Introductionmentioning
confidence: 99%